The Changes in Cross-Resistance, Fitness, and Feeding Behavior in Aphis gossypii as Their Resistance to Sulfoxaflor Declines - Mingyuan Lv; Wei Wang; Fengyun Fang; Xiaowei Fu; Gemei Liang (Insects)
The increasing resistance in Aphis gossypii field populations to sulfoxaflor and many different types of insecticides represents a significant challenge in protecting cotton production in China. Although resistant pests were able to regain their susceptibility to insecticides after the reduction in insecticide applications, some of their biological parameters remained different from susceptible strains. The resistance to sulfoxaflor was unstable in A. gossypii after the loss of selective pressure. The strain with declined resistance (Sul-D) (RR = 1.11-fold) restored its susceptibility to sulfoxaflor, acetamiprid, and imidacloprid after the sulfoxaflor-resistant (Sul-R) (RR = 51.57-fold) was maintained without insecticide pressure for 22 generations. Sul-R had a relative fitness of 0.87, and the Sul-D strain still had a relative fitness of 0.84, even if its susceptibility to sulfoxaflor was restored. Compared with the susceptible strain (Sus), the Sul-R and Sul-D strains became more active in searching for appropriate feeding positions because they generated more intercellular apoplastic stylar pathway events (C). However, the phloem-feeding ability was reduced in the Sul-R and Sul-D strains, as shown by the decrease in phloem behavioral parameters, such as phloem salivations (E1), phloem ingestion (E2), and the percentages of E1 and E2. The negative hormesis effect of sulfoxaflor on phloem feeding was observed in susceptible strain but not in Sul-R and Sul-D, as evidenced by the significant decreases in the number of E1, the duration of E1 and E2, and the percentage of E1 and E2 in the Sus strain. Sulfoxaflor resistance was unstable in A. gossypii, and there was still a fitness cost to A. gossypii after recovering susceptibility to sulfoxaflor. The phloem-feeding ability was reduced in the Sul-R and Sul-D strains compared with the Sus strain, but the negative hormesis effect of sulfoxaflor on phloem feeding was only found in the Sus strain. The outcomes of this study could contribute to a comprehensive risk assessment and provide a basis for developing a better strategy to control A. gossypii.